The complete project manager : integrating people, organizational, and technical skills - Englund, Randall L. (Management Concepts Press, 2012)
Get proven procedures to overcome project challenges The Complete Project Manager: Integrating People, Organizational, and Technical Skills is the practical guide that addresses the "soft" project management skills that are so essential to successful project, program, and portfolio management. Through a storytelling approach, the authors explain the necessary skills-and how to use them-to create an environment that supports project success. They demonstrate both the "why" and the "how" of creatively applying soft project management skills in the areas of leadership, conflict resolution, negoti